Evaluation of accidental radioactive ’atmospheric discharges by nuclear reactors - Graça, Cláudio de Oliviera (Ciência e Natura, 2002)
The primary consideration concerning the safety of a nuclear installation refers to the protection of operators and the surrounding public both during normal operation as well as during an accidental release of radioactive contaminants into the atmosphere. The nuclear electricity generation has proved to be a safe technology, despite the generation of an enormous quantity of radioactive isotopes, both actinides and products of activation, considering the small number of accidental atmospheric dispersion events. In modern reactor installations like that of Angra I in Brazil, the monitoring of radioactivity has not lead to radioactive levels higher than normal accepted environmental levels. This is a consequence of safety features built into the plant in order that, should there be a radioactive release, no members of the public would be subjected to unacceptable levels of risk. Since there have been a very few number of reported reactor accidents, the design of a nuclear plant must resort to theoretical calculations and simulations of hypothetical releases to study the consequences of accidental dispersion of radioactive effluents. In this paper we consider the various stages related with the release of radioactivity from the irradiated nuclear fuel to the calculation of doses, starting from the radioactive inventory calculation followed with the model of radioactive release and the standard treatment for the effluents behavior in the atmosphere suggesting the gamma doses calculation to the public based in the use of the adjoint flux calculations, used as importance function, instead of the direct calculation. This new methodology will be more effective, considering the inherent large uncertainties in each stage of the radioactive release and dispersion computations. It is also necessary to remember that the system of dose limitation is based on maximum allowed levels of accidental release and maximum pollutants concentration (MCP) on air or on water and in this case the adjoint flux takes the function of the Importance of a particular radioactive release for the dose received by each irradiated individual, or for any other integral response.